Peserta Didik dalam Pendidikan Perspektif Ibnu Sina - Rumza Amalia; Zahwatul Khusna; Aisyah Nanda Salsabila; Moh. Faizin (Indo Publishing, 2026)
The requirements of Islamic education today are very relevant to Ibn Sina's ideas about education. According to Ibn Sina, education is a way to create a complete human being—physically, intellectually, socially, and spiritually—not merely a method to transmit knowledge. He emphasized the importance of achieving a balance between moral and ethical development and mastery of knowledge. He believed that in addition to intelligence, a student needs to have a positive attitude, be honest, and take responsibility both for the environment and for themselves. This concept becomes highly relevant in the context of Islamic education today due to the challenges posed by globalization and modernization, which often overshadow spiritual principles. Islamic education must provide an integrative curriculum that combines general knowledge, religious understanding, and life skills in accordance with contemporary developments. Moreover, the core of the entire educational process must be character education. It is estimated that by adopting the principles of Ibn Sina, a new generation of morally upright and intellectually intelligent individuals will emerge, capable of making significant contributions to the advancement of civilization and humanity.